Sodium-stimulated alpha-aminoisobutyric acid transport by membrane vesicles from simian virus-transformed mouse cells. - Hamilton, R T (1976)
Uptake of alpha-aminoisobutyric acid, by membrane vesicles derived principally from the plasma membrane and endoplasmic reticulum of mouse 3T3 cells transformed by simian virus 40, is stimulated by sodium chloride. Both in the presence and absence of Na+ uptake is time-dependent and osmotically sensitive. The Na+-stimulated uptake is inhibited by other amino acids. The kinetics of transport of alpha-aminoisobutyric acid are shown to be biphasic both in whole cells and in the membrane vesicles. Only the high affinity system is stimulated by sodium in the membrane vesicles. These results demonstrate that observations made on living cells correlate with observations made on isolated membrane vesicles, and indicate that these membrane vesicles have retained the cellular amino acid transport system functionally intact.